PEMODELAN ESTIMASI BIAYA KONTINGENSI BERBASIS RESIKO PADA PROYEK ENGINEERING-PROCUREMENT-CONSTRUCTION - Wahyu Adi, Tri Joko; Yunwanti, Suly (Jurusan Teknik Sipil Universitas Tadulako, 2014)
EPC (Engineering-Procurement-Construction) Project is a project in which the process of design, procurement and construction are carried out by a construction company. The complexity of EPC project resulted in many uncertainties that must be addressed by the project implementers. To anticipate the risk of cost overruns due to the uncertainty, project implementers need to prepare the unexpected costs. Currently, implementation of contingency estimation is done by directly increasing project costs by 5% -10%; while in theory, the amount of the contingency cost is estimated using Montecarlo simulation techniques. This simulation techniques, despite widely used, still has the disadvantage. Risks are assumed by providing lower and upper limit values of the cost of the risks that might occur in the project activity. In fact, every activity has different risk and different weights of impact. The objective of this research is to create a contingency-based cost estimation model by considering the types of risk and its impact on project activity. Project Risks were obtained from preliminary surveys and literature studies. Probability weights were analyzed using probability-Impact matrix and pair-wise comparison. Contingency cost calculation was done using Montecarlo simulations. For the purpose of model validation, procurement & Gas Piping Distribution project in Greater Jakarta was used as case study. The results of case study simulation showed that the contingency cost is 4.57% of the project budget, with a deviation of 0.82%. The accuracy test of the model against the actual cost of the project showed 0.63% difference to the simulation results. Therefore the proposed model is proved has good accuracy. Keywords: risk analysis, contingency cost,Â Montecarlo Simulation, EPC Project